2002
DOI: 10.1103/physrevb.66.073403
|View full text |Cite
|
Sign up to set email alerts
|

Chirality in bare and passivated gold nanoclusters

Abstract: Chiral structures have been found as the lowest-energy isomers of bare (Au 28 and Au 55 ) and thiol-passivated ͓Au 28 (SCH 3 ) 16 and Au 38 (SCH 3 ) 24 ] gold nanoclusters. The degree of chirality existing in the chiral clusters was calculated using the Hausdorff chirality measure. We found that the index of chirality is higher in the passivated clusters and decreases with the cluster size. These results are consistent with the observed chiroptical activity recently reported for glutahione-passivated gold nano… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
216
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(226 citation statements)
references
References 26 publications
6
216
1
3
Order By: Relevance
“…1a) was transformed into much less symmetric configurations of lower energy. The energy lowering is quite substantial, more than 2 eV, instead of the 0.3 to 0.6 eV lowering found by Garzón et al for their C s model 22,23 . After a local minimum with one adatom sticking out (Fig.…”
Section: Fig 1 (Color Online)contrasting
confidence: 53%
See 1 more Smart Citation
“…1a) was transformed into much less symmetric configurations of lower energy. The energy lowering is quite substantial, more than 2 eV, instead of the 0.3 to 0.6 eV lowering found by Garzón et al for their C s model 22,23 . After a local minimum with one adatom sticking out (Fig.…”
Section: Fig 1 (Color Online)contrasting
confidence: 53%
“…The authors found that the global minima are amorphous in nature with an Au 4 tetrahedron core and a much bigger outer-shell for Au N with N > 32. Using an empirical potential for global minimum search followed by density functional theory (DFT) calculations, Garzón et al found that the most stable structure of Au 38 is of C s symmetry with an Au 5 core 22,23 . This structure was found to be slightly lower in energy than the high-symmetry truncated octahedron (by about 0.3 to 0.6 eV, depending on the choice of DFT functional 22,23 ).…”
mentioning
confidence: 99%
“…Also this topology is cage-like as the previous one, but it loses symmetry and drops to point group C 1 being therefore chiral. Chirality seems a frequently occurring phenomenon for gold clusters and has been observed by several researchers [82][83][84][85][86][87][88][89][90]. (Table I).…”
Section: Au 12mentioning
confidence: 99%
“…The majority of chiral metal nanoclusters known to date are of types (a) [27][28][29][30][31][32][33][34][35][36] and (b) 16,17,[37][38][39] , with a few belonging to types (c) and (d). [40][41][42] As prepared, many of these chiral metal nanoclusters (types b-d) are racemic mixtures that require separation and purification by various optical resolution methods. Enantioseparation of Au nanoclusters (e.g., Au28, Au38, Au40) has been reported by using chiral HPLC columns.…”
mentioning
confidence: 99%